The Influence of Financial Literacy, Financial Attitude, Financial Inclusion, Locus of Control on MSMEs Performance Case Study in Jabodetabek Area - Telaumbanua, Calvin Mandala Saputra; Purwanto, Purwanto (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
The research objectives to examine financial literacy, financial attitude, financial inclusion, locus of control on MSMES performance mediated by financial management behavior focusing on MSMEs businesses in the Jabodetabek area. This research is quantitative with the SEM-PLS completion method to analyze factors that influence MSME performance from a financial perspective. The data used is primary data, received responses from 311 respondents spread across Jabodetabek using 4 independent variables, namely Financial Literacy, Financial Inclusion, Locus of Control, Financial Attitude, one dependent variable namely MSMEs Performance with Financial Management as intervening. This research uses a non-probability sampling method to reach respondents who meet the requirements of the selected criteria. The results of the research state that all independent variables have a significant positive influence on Financial Management and MSMEs Performance.